The effect of Ba Duan Jin exercise intervention on cardiovascular disease: a meta-analysis of randomized controlled trials - Jiali Chen; Man Zhang; Yihao Wang; Ziyu Zhang; Shuyan Gao; Yafei Zhang (Frontiers Media S.A., 2024)
BackgroundThere is a growing interest in the use of complementary therapies for the prevention of disease and the maintenance of health. Furthermore, complementary therapies that incorporate exercise are becoming increasingly prevalent among the older adult, and thus may represent a crucial strategy for the primary and secondary prevention of cardiovascular disease (CVD). Exercise therapy, as a means to prevent and treat cardiovascular diseases, has been gradually applied in clinical practice. It has the advantages of reducing mortality, improving clinical symptoms, restoring physical function and improving quality of life. In recent years, traditional Chinese sports such as Ba Duan Jin and Qigong have developed rapidly. Therefore, a comprehensive systematic review is required to examine interventions involving Ba Duan Jin exercise in healthy adults or those at increased risk of CVD in order to determine the effectiveness of Ba Duan Jin exercise for the primary prevention of CVD.ObjectiveTo investigate the effect of Ba Duan Jin exercise intervention for the primary prevention of cardiovascular diseases.MethodsEight databases were systematically searched from inception to July, 2024 for randomized controlled trials (RCTs) to evaluated the impact of Ba Duan Jin exercise intervention on cardiovascular diseases. The search terms were "Cardiovascular diseases" "Ba Duan Jin" and "Randomized controlled." The Cochrane risk assessment tool was used to evaluate the study quality, and the meta-analysis was performed using Rev. Man 5.4 software.ResultsSeventeen completed trials were conducted with 1,755 participants who were randomly assigned and met the inclusion criteria. All 17 studies were conducted in China. The meta-analysis indicates that Ba Duan Jin exercise therapy can provide long-term benefits (20-30 years) by reducing all-cause mortality (RR = 0.55, 95% CI: 0.44-0.68, p < 0.01) and stroke mortality (RR = 0.49, 95% CI: 0.36-0.66, p < 0.01) in hypertensive patients. Subgroup analyses reveal that Ba Duan Jin exercise therapy decreases SBP (MD = −4.05, 95% CI = −6.84 to −1.26, p < 0.01) and DBP (MD = −3.21, 95% CI = −5.22 to −1.20, p < 0.01) levels in patients with essential hypertension, significantly reduces serum TC (MD = −0.78, 95% CI = −1.06 to −0.50, p < 0.01), TG (MD = −0.78, 95% CI = −0.93 to −0.62, p < 0.01), and LDL-C (MD = −0.76, 95% CI = −0.92 to −0.60, p < 0.01) levels in patients with hyperlipidemia, increases HDL-C (MD = 0.32, 95% CI = 0.14-0.51, p < 0.01) levels, and produces beneficial effects on cardiovascular function. Additionally, it can alleviate anxiety (MD = −3.37, 95% CI = −3.84 to −2.89, p < 0.01) and improve sleep quality (MD = −2.68, 95% CI = −3.63to −1.73, p < 0.01).ConclusionBa Duan Jin exercise therapy can improve the physical and mental condition and quality of life of patients with cardiovascular diseases, and it is worthy of further promotion and application in clinical practice.Systematic review registrationPROSPERO, identifier: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024496934.